Enhancing the efficiency of photovoltaic cells through the usage of dye concentrators - Brągoszewska, Ewa; Bogacka, Magdalena; Wajda, Agata; Milewicz, Bartłomiej (Frontiers in Energy Research, 2024)
Over the past few years, there has been a growing interest in renewable energy sources. Among them, photovoltaic (PV) technology is advancing rapidly. Solar insolation is the most crucial factor for PV installations. Various solutions, such as tracking mechanisms, hybrid systems, and new materials, can enhance the efficiency of PV systems. Concentrators focus solar light onto the surface of solar modules, increasing production of electricity. Implementing such solutions can reduce the number of silicon cells in installations, leading to a decrease in waste generated during production. Dye concentrators have a positive impact on the performance of silicon systems. A two-stage study on the effect of dye concentrator application on PV cell efficiency is carried out. In the first stage, specific types of dye concentrators are tested for their interaction with the silicon system. Tinted and luminescent acrylic glass (polymethyl methacrylate, PMMA) in yellow and red are used as dye concentrators. The experiment included multiple measurement calibrations, such as the temperature of the tested silicon cell and the intensity of illuminance. Results showed an efficiency absolute increase of efficiency in solar cells ranging from 0.05% to 1.42%, depending on the type of concentrator used. The most significant improvements were observed with luminescent red PMMA, averaging at 1.21%. The potential of this concentrator was further explored in the second stage of the study, investigating the relationship between the surface involvement of the silicon cell and the dye concentrator. Test results indicated the potential of dye concentrators for integrating luminescent dye concentrator technology into PV systems. The effect of this integration is increase in the efficiency of the PV cell. On the other hand, it should be noted that replacing the PV cell with a dye concentrator reduces the efficiency of the entire photovoltaic system. Hence, the use of a PV cell and concentrator system is recommended especially for photovoltaic systems with a large area. As dye concentrators have the ability to operate without direct irradiance, they are also recommended for regions where natural light is dispersed.